THE INFLUENCE OF VILLAGE FUNDS, SPENDING ON SOCIAL PROTECTION FUNCTIONS, AND CAPITAL EXPENDITURES ON THE REGIONAL REVENUE AND EXPENDITURE BUDGET ON POVERTY LEVELS IN INDONESIA - Suranto, Suranto; Miru, Sulaeman; Hatma, Ramli (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2021)
This research aims to determine how the influence of village funds, local government spending through spending on social protection functions, and capital expenditures on poverty levels in Indonesia. This research method uses the Multiple Linear Regression method to determine the influence between variables. The data type used is quantitative data, and the data source is secondary data from the Ministry of Finance and the Central Statistics Agency. First, the results explain a significant negative effect of the Village Fund on the poverty level in Indonesia, meaning that if the allocation of village funds is increased, the poverty rate will decrease. The following result is that there is a significant negative effect of spending on social protection functions on the level of poverty in Indonesia, meaning that if spending on social protection functions is increased, the poverty rate will decrease. Finally, there is a significant negative effect of capital expenditure on the Regional Revenue and Expenditure Budget of Poverty level in Indonesia, meaning that if capital expenditures on regional income budget allocation are increased, the poverty rate will decrease. Keywords : Village Fund Allocation, Social Protection Function Expenditure, Capital Expenditure, Poverty Level.